The Health Impacts from Living Near Economic Industrial Parks in Sumatera - Sunjaya, Evan; Yudhistira, Muhammad Halley (International Journal of Economics Development Research (IJEDR), 2025)
While the operation of industrial areas has positively contributed to local economic growth on Sumatra Island, it has also resulted in negative environmental and health impacts. These externalities have prompted government intervention to address the adverse effects. Previous research indicates the need for alternative methods to quantify the side effects of industrial operations. This study, using Podes data and the Two-Way Fixed Effect (TWFE) model, estimates the impact of industrial activities on local health, specifically examining the incidence of diarrheal outbreaks as a proxy indicator at the village level. The analysis finds that industrial activities are positively correlated with a 4.16% increase in the incidence of diarrheal outbreaks in villages located within a 0 to 10 km radius of industrial areas, with statistical significance at the 1% level.